Chemical-functional characterization of Ascophyllum nodosum and Phymatolithon calcareum and dietary supplementation in post-weaning pigs - Frazzini, Sara; Reggi, Serena; Dell’Anno, Matteo; Fifi, Anna Paola; Scaglia, Elena; Ferri, Irene; Rossi, Luciana (Frontiers in Veterinary Science, 2024)
IntroductionAs the livestock industry grapples with the need for sustainable land, maintaining production systems, and reducing antimicrobial resistance, the application of functional nutrition emerges as a potential solution.AimIn line with the One Health principles, this study aims to evaluate functional properties of Ascophyllum nodosum and Phymatolithon calcareum, and assess the effects of their dietary supplementation on piglets’ health.Materials and methodsA chemical-functional characterization was conducted before and after in vitro digestion. Total Polyphenols Content (TPC) and Total Flavonoid Content (TFC) were determined through colorimetric assays, while antioxidant activity was determined using ABTS assay, and the microdilution method was used to evaluate the antimicrobial capacity. For the in vivo trial twenty-four post-weaning pigs (28 ± 2 days, 6.89 ± 0.820 Kg) were enrolled in two homogeneous groups (n = 12/group): control group (CTRL) fed a commercial diet, and treated group (ALGAE) fed commercial diet with the addition of 1.5% of A. nodosum and 0.5% of P. calcareum for 27 days. Weekly, zootechnical performances were assessed monitoring the body weight and the individual feed intake. Fecal samples were collected to evaluate the abundance of total, lactic acid and coliform bacteria through plate counting. Serum were obtained at day 0 and day 27 to assess the antioxidant barrier.Results and discussionThe chemical characterization discloses that the minerals’ level remains below the maximum thresholds defined for their use in piglets nutrition. TPC was 330.42 ± 21.372 mg TAE/g of the sample and 11.45 ± 0.521 mg TAE/g of the sample for A. nodosum and P. calcareum, respectively, and a similar trend was found in the TFC evaluation (213.85 ± 20.557 and 2.71 ± 0.900 mg CE/g of sample, respectively). Our results also highlighted that polyphenols and flavonoid compounds persisted after in vitro digestion as well as the functional properties. The administration of algae in piglets diet, although it slightly affected feed efficiency in the first period of the trial, did not affect the animal growth in terms of weight and average daily gain. Microbiological analysis of feces showed similar values between the two experimental groups over 27 days. A significantly higher serum antioxidant barrier was registered in ALGAE compared to CTRL group at day 27 (363.26 ± 16.241 vs. 230.69 ± 32.078 HClO/mL, p < 0.05).ConclusionIn conclusion, the supplementation with A. nodosum and P. calcareum could be considered a promising dietary strategy to enhance the oxidative barrier in weaned piglets.